THEOLOGICAL ASPECTS OF THE BRAZILIAN STRICTO SENSU ACADEMIC PRODUCTION ON HOSPITAL CHAPLAINCY - Cordeiro de Souza, Anselmo; Oliveira, Izabel Maria de; Rodrigues Chaves, Jolivê (Práxis Teológica, 2021)
This article presents a descriptive approach whose objective is to explain theological models present in academic publications (theses and dissertations). It is not intended to be a systematic analysis or even a hermeneutic-exegetical study, but rather a narrative approach to the theologies present in the consulted material. This is a narrative review of the literature, and the steps for elaboration and organization derived from other studies. It was operationalized according to the following steps: identification of the theme, bibliographic survey, selection of texts, annotations, preliminary structuring and logical structuring of the study. We sought to provide an understanding of current knowledge on the theme “hospital chaplaincy”, highlighting possible gaps and suggesting an agenda of investigations to be undertaken. The TQO strategy (theme, qualifier, object) was used to formulate the research question, which is indicated for narrative reviews, resulting in the issue: which theological models are present in theses and dissertations available in the Brazilian context? The searches were online in the theses and dissertations database of the Coordination for the Improvement of Higher Education Personnel (Capes), carried out in 2020, using the descriptor “chapel*/hospital chaplaincy”, without restrictions on the year of publication or any other. The titles of interest related to the theme were included, in order to answer the proposed question. Data were organized in tables, with qualitative and quantitative summaries. Thirteen productions were retrieved. Among the main results, it is highlighted that approaches of anthropological and praxiological origin prevailed, associated with theological models/concepts such as “imago Dei”, “poimenics” and “theodicy”.